2008
DOI: 10.1111/j.1600-0501.2008.01524.x
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of salivary and serum proteins, and bacterial adherence on titanium and zirconia ceramic surfaces

Abstract: The pellicles were formed in vitro by incubating the materials with whole saliva, serum or saliva+serum. Protein composition in each of the pellicles was investigated by SDS-PAGE and immunodetection. The adherence of radiolabeled Streptococcus mutans and Actinomyces naeslundii to uncoated surfaces and experimental pellicles was determined by means of scintillation counting. Statistical analyses were done using ANOVA and Tukey's test at significance level at P<0.05. In general, the electrophoretic analysis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
73
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 47 publications
6
73
0
Order By: Relevance
“…In the present study, no differences in initial attachment were recognized among the specimens in the Saliva+ groups. This finding may be supported by an earlier study which found that similar types of salivary protein attached to Ti and zirconia 41) . In the present study, no attempt was made to evaluate the content of saliva proteins.…”
Section: Discussionsupporting
confidence: 81%
“…In the present study, no differences in initial attachment were recognized among the specimens in the Saliva+ groups. This finding may be supported by an earlier study which found that similar types of salivary protein attached to Ti and zirconia 41) . In the present study, no attempt was made to evaluate the content of saliva proteins.…”
Section: Discussionsupporting
confidence: 81%
“…This is in line with the results found by Lima et al who stated that pre-coating of titanium surfaces with experimental salivary pellicle, did not affect the adherence of A. naeslundi [22]. However, in that study, the bacteria were suspended in nutrient broth and not in saliva.…”
Section: Titanium Specimensupporting
confidence: 91%
“…In contrast, it has been reported that other strains of S. oralis bind well to a range of saliva-coated dental materials (Meier et al, 2008), as seen for LA11 and 89C. Other oral streptococci such as S. mitis, S. sanguinis or S. mutans have also been reported to show different binding in different studies, with some reporting decreased levels (Ahn et al, 2002;Lima et al, 2008;PrattTerpstra et al, 1989;Mei et al, 2011) in the presence of saliva and others reporting enhanced adherence (Nikawa et al, 2006). Thus, overall, the data suggest that differences between strains of oral streptococci may be as great as those between streptococcal species.…”
Section: Discussionmentioning
confidence: 74%
“…Studies of pellicle formation have suggested that the salivary proteins amylase, immunoglobulin A and proline-rich proteins (Edgerton et al, 1996;Lima et al, 2008), as well as albumin and fibronectin, can bind to titanium (Lima et al, 2008). Pellicle proteins serve as receptors for the attachment of micro-organisms that initiate the formation of a microbial biofilm (Murray et al, 1992;Kolenbrander et al, 2010).…”
Section: Introductionmentioning
confidence: 99%